The importance of educational activities in prostate cancer awareness: blue November (Research, Society and Development, 2021)
Prostate cancer is the most common type among men. The prostate is a gland that only a man has and that is located in the lower abdomen. This is a descriptive study, of the experience report type, carried out in a basic health unit in the State of Pará. men's resistance to continuing periodic consultations, therefore, an activity was carried out with the aim of developing the health-disease process, to meet the specific target audience of men of prostate cancer screening age. The intention was to acquire a greater number of adherence of patients from the male health unit to screening. Thus, multidisciplinary care is important so that all teaching axes can be sought to be passed on to the community, so that educational actions together clarify forms of prevention and provide an early diagnosis.